Nature or Nurture in Finger Counting: A Review on the Determinants of the Direction of Number–Finger Mapping - Previtali, Paola; Rinaldi, Luca; Girelli, Luisa (Frontiers in Psychology, 2011)
The spontaneous use of finger counting has been for long recognised as critical to the acquisition of number skills. Recently, the great interest on space-number associations shifted attention to the practice of finger counting itself, and specifically, to its spatial components. Besides general cross-cultural differences in mapping numbers onto fingers, contrasting results have been reported with regard to the directional features of this mapping. The key issue we address is to what extent directionality is culturally-mediated, i.e., linked to the conventional reading-writing system direction, and/or biologically determined, i.e. linked to hand dominance. Although the preferred starting hand for counting seems to depend on the surveyed population, even within the same population high inter-individual variability minimises the role of cultural factors. Even if so far largely overlooked, handedness represents a sound candidate for shaping finger counting direction. Here we discuss adults and developmental evidence in support of this view and we reconsider the plausibility of multiple and coexistent number-space mapping in physical and representational space.